Leading in Entrepreneurial Universities: Do Demographics Display Different Commitments? - Fatimah, Fatimah; Sarbaini, Sarbaini; Arisanty, Deasy (Frontiers in Education, 2022)
For the excellence of universities as instructional institutions, lecturers’ dedication has been extensively acknowledged as a productive trajectory. Since public university in Indonesia remains the most influential spot leading to the growth of a nation, it needs dedicated lecturers as strategic partners. This study spots the contemporary dedication of lecturers beneath dimensions of affective, continuance or normative and discover whether or not there is any tremendous variance between chosen demographics over organizational dedication questions. The information had been received from 500 full-time lecturers serving public universities of Indonesia. The finding indicates that most lecturers possess continuance commitment, for they calculate the prices and advantages associated to no longer serving the university. Further, when better options are available, they will leave their universities. From the selected demographic variables examined, solely the level of education and length of service significantly affect the commitment of university teachers. This study discloses that the lecturers and the universities are engaged in a reciprocal relationship. When lecturers are professionally treated, they respond with a more outstanding commitment as they discover them as a necessary section of the organization. Consequently, universities rely on dedicated lecturers to create and sustain a competitive advantage in maintaining world ranking.